2024
DOI: 10.3390/toxins16010024
|View full text |Cite
|
Sign up to set email alerts
|

Jelleine, a Family of Peptides Isolated from the Royal Jelly of the Honey Bees (Apis mellifera), as a Promising Prototype for New Medicines: A Narrative Review

William Gustavo Lima,
Julio Cesar Moreira Brito,
Rodrigo Moreira Verly
et al.

Abstract: The jelleine family is a group of four peptides (jelleines I–IV) originally isolated from the royal jelly of honey bee (Apis mellifera), but later detected in some honey samples. These oligopeptides are composed of 8–9 amino acid residues, positively charged (+2 to +3 at pH 7.2), including 38–50% of hydrophobic residues and a carboxamide C-terminus. Jelleines, generated by processing of the C-terminal region of major royal jelly proteins 1 (MRJP-1), play an important biological role in royal jelly conservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 100 publications
0
0
0
Order By: Relevance
“…An overview of the molecular and cellular mechanisms of RJ is shown in Table 5, while the doses of RJ used in some clinical trials are shown in Table 6. [307] RJ − reduces oxidative stress and levels of IL-6, IL-8, and TNF-α [292,298,299,[327][328][329][330][331] Note: Aβ, amyloid beta; ACE, angiotensin-converting enzyme; Ach, acetylcholine; Akt, protein kinase B; ALP, alkaline phosphatase; ALT, alanin-aminotransferase; AMPK, AMP-activated protein kinase; anti-OVA, antibodies that detect ovalbumin; AP-1, Activator protein 1; ApoA-I, apolipoprotein A-I; Apo-B, apolipoprotein B; APP, amyloid precursor protein; ARE, antioxidant response element; AST, aspartate aminotransferase; ATF4, activating transcription factor-4; ATM, ataxia telangiectasia-mutated; ATR, ataxia telangiectasia-mutated and Rad3-related; BACE1, beta-site APP cleaving enzyme 1; BAT, brown adipose tissue; Bax, Bcl-2associated X protein; BBB, blood-brain barrier; Bcl-2, B-cell lymphoma- mTOR, mammalian target of rapamycin; MUC2, mucin; NaMN, nicotinic acid mononucleotide; NEP, neprilysin; NFAT c1, nuclear factor of activated T cell; NF-κB, nuclear factor kappa-light-chain-enhancer of activated B cells; NGF, nerve growth factor; NLRP1, NOD-like receptor (NLR) family pyrin domain-containing 1; NO, nitric oxide; Nrf2, nuclear factor E2-related factor 2; OPG, osteoprotegerin; Osx, Osterix; OVX, ovariectomy; PGC-1α, peroxisome proliferator-activated receptor-γ coactivator-1 alpha; PI3K, phosphatidylinositol 3-kinase; PPAR-γ, peroxisome proliferator-activated receptor gamma; PTEN, phosphatase and tensin homolog; RAGE, receptor for advanced glycation end products; RANK, receptor activator of nuclear factor-κB; RANKL, receptor activator of NF-κB ligand; RB, retinoblastoma gene; RCC, renal cell carcinoma; ROS, reactive oxygen species; RUNX2, runt-related transcription factor 2; S6K1, S6 kinase 1; SASP, senescenceassociated secretory phenotype; SCFAs, short-chain fatty acids; SOD, superoxide dismutase; T, Testosterone; T3, triiodothyronine; T4, thyroxine; TC, total cholesterol; TGF-β, transforming growth factor-beta; TNF-α, Tumor Necrosis Factor alpha; TNBS, 2, 4,6-trinitrobenzene sulfonic acid; TRP-1, tyrosinase-related protein 1; TRP-2, tyrosinase-related protein 2; TSH, thyroid stimulating hormone; UCP1, uncoupling protein 1; VLDL-C, very-low-density lipoprotein cholesterol; VSMCs, vascular smooth muscle cells. For premature babies 50 mg to 1 g per day − growth and development − strengthen immunity and nervous system [6] Children:…”
Section: Closing Remarksmentioning
confidence: 99%
See 4 more Smart Citations
“…An overview of the molecular and cellular mechanisms of RJ is shown in Table 5, while the doses of RJ used in some clinical trials are shown in Table 6. [307] RJ − reduces oxidative stress and levels of IL-6, IL-8, and TNF-α [292,298,299,[327][328][329][330][331] Note: Aβ, amyloid beta; ACE, angiotensin-converting enzyme; Ach, acetylcholine; Akt, protein kinase B; ALP, alkaline phosphatase; ALT, alanin-aminotransferase; AMPK, AMP-activated protein kinase; anti-OVA, antibodies that detect ovalbumin; AP-1, Activator protein 1; ApoA-I, apolipoprotein A-I; Apo-B, apolipoprotein B; APP, amyloid precursor protein; ARE, antioxidant response element; AST, aspartate aminotransferase; ATF4, activating transcription factor-4; ATM, ataxia telangiectasia-mutated; ATR, ataxia telangiectasia-mutated and Rad3-related; BACE1, beta-site APP cleaving enzyme 1; BAT, brown adipose tissue; Bax, Bcl-2associated X protein; BBB, blood-brain barrier; Bcl-2, B-cell lymphoma- mTOR, mammalian target of rapamycin; MUC2, mucin; NaMN, nicotinic acid mononucleotide; NEP, neprilysin; NFAT c1, nuclear factor of activated T cell; NF-κB, nuclear factor kappa-light-chain-enhancer of activated B cells; NGF, nerve growth factor; NLRP1, NOD-like receptor (NLR) family pyrin domain-containing 1; NO, nitric oxide; Nrf2, nuclear factor E2-related factor 2; OPG, osteoprotegerin; Osx, Osterix; OVX, ovariectomy; PGC-1α, peroxisome proliferator-activated receptor-γ coactivator-1 alpha; PI3K, phosphatidylinositol 3-kinase; PPAR-γ, peroxisome proliferator-activated receptor gamma; PTEN, phosphatase and tensin homolog; RAGE, receptor for advanced glycation end products; RANK, receptor activator of nuclear factor-κB; RANKL, receptor activator of NF-κB ligand; RB, retinoblastoma gene; RCC, renal cell carcinoma; ROS, reactive oxygen species; RUNX2, runt-related transcription factor 2; S6K1, S6 kinase 1; SASP, senescenceassociated secretory phenotype; SCFAs, short-chain fatty acids; SOD, superoxide dismutase; T, Testosterone; T3, triiodothyronine; T4, thyroxine; TC, total cholesterol; TGF-β, transforming growth factor-beta; TNF-α, Tumor Necrosis Factor alpha; TNBS, 2, 4,6-trinitrobenzene sulfonic acid; TRP-1, tyrosinase-related protein 1; TRP-2, tyrosinase-related protein 2; TSH, thyroid stimulating hormone; UCP1, uncoupling protein 1; VLDL-C, very-low-density lipoprotein cholesterol; VSMCs, vascular smooth muscle cells. For premature babies 50 mg to 1 g per day − growth and development − strengthen immunity and nervous system [6] Children:…”
Section: Closing Remarksmentioning
confidence: 99%
“…Insects only recently became interesting to scientists as fat tissue and other insect cells produce numerous antimicrobial peptides that can be found in their hemolymph. Antimicrobial peptides (AMPs) are also present in RJ [ 48 , 63 , 68 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 ]. In addition to antibacterial activity, these peptides show antiviral, antitumoral, immunoregulatory, and hepatoprotective effects as well.…”
Section: Biological Function Of Royal Jellymentioning
confidence: 99%
See 3 more Smart Citations